(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background:Platelet parameters are significant, especially in diagnosis of causes of thrombocytopenia. The platelet parameters are widely available as part of full blood count with no extra cost. Thrombocytopenia is of varying etiology, it is broadly divided into three major categories (1) as increased destruction (ITP), (2) decreased production and (3) splenic sequestration/abnormal pooling. Aims of the study: To investigate the indices of the platelets which include ( MPV,PDW,PCT) and to signify its role in the diagnosing the etiology of thrombocytopenia, if there is any correlation between platelet count and platelets indices and to determine cut off point of MPV for the diagnosis of ITP. Materials and Methods: 104 cases of Thrombocytopenia (TCP) and 50 control cases having normal platelet count were selected. TCP was defined as platelet count <150 x 109/L. Analysis was done by Diagon cell counter and every case was reassessed by Peripheral Smear (P.S.) examination and if necessary also by manual method. Only those cases that had sufficient clinico-hematological work -up and the causes of low platelet count had been reliably established were included in the study. Results: The study was conducted on 104cases they were broadly categorized into three groups Group A with reduced production, Group B with increased destruction and Group C with abnormal pooling(splenomegaly). In group A, mean platelets count 64.98 x 109/l ± 36.5, mean MPV 9.3 Fl ± 1.1 , mean PDW 16.33 Fl±0.73, mean PCT 0.094% ± 0.157, M:F ratio1:1, there were a significant statistical difference in platelets count with control group (P value 0.000) and with group B (p value 0.0420), mean MPV shows significant difference with all control, B and C groups (P value 0.000, 0.000, 0.01 respectively), PDW also shows significant difference with control and C groups ( p value 0.000, 0.001 respectively), PCT shows significant statistical difference with control and B groups ( p value 0.000, 0.04) respectively. There was a negative correlation platelets count and PDW. In group B, mean platelets count 44.51 x 109/l ± 33.9, mean MPV 10.3 Fl ± 1.5, mean PDW 16.22 Fl ±0.86, mean PCT 0.049% ± 0.042, M:F ratio 1:4.5, there were a significant statistical difference in platelets count with control group (P value 0.000), with group A (p value 0.0420) and with group C (p value 0.006), MPV shows significant statistical difference with all groups (P value 0.000 for all), PDW shows significant difference with control and C groups (p value 0.000, 0.008 respectively) , PCT with control and group A (p value 0.000, 0.04) respectively. There was a negative correlation platelet count and MPV and PCT. A cut off point for the diagnosis of ITP is 9.9 with 100% sensitivity and 100 % specificity. Regarding group C, mean platelets count 80.0 x 109/l ± 27.1, mean MPV 8.5 Fl ± 0.84 , mean PDW 15.67 Fl ± 0.84, mean PCT 0.1007% ± 0.139, M:F ratio 1:1.1, there were a significant statistical difference in platelets count with control group (P value 0.000) and group B (p value 0.006), mean MPV shows significant difference with group A and B groups (P value 0.01, 0.000 respectively), PDW shows significant difference with group A and B groups (p value 0.001, 0.008 respectively), while PCT shows significant statistical difference with control and B groups only (p value 0.000,0.08) respectively. There was no correlation between platelet count and its parameters. Conclusion: Platelet indices are useful method to distinguish immune thrombocytopenia from hypoproductive thrombocytopenia and can provide significant data about the underlying causes of thrombocytopenia. MPV can discriminate ITP from hypoproductive thrombocytopenia and cut off point is 9.9 FL and they may postpone ITP patients from doing bone marrow aspiration and to ovoid platelet transfusion, there is negative correlation between MPV and platelets count in ITP patients.